Lusitania : an epic tragedy - Preston, Diana, 1952- (New York : Walker & Co., 2002)
An account of the 1915 sinking of the Lusitania offers a portrait of early twentieth-century maritime history and the terrible impact of the disaster on the course of World War I.
Prologue -- pt. 1. Troubled waters -- ch. 1. A scrap of paper -- ch. 2. The weapon of the weaker nation -- ch. 3. More beautiful than Solomon's temple -- ch. 4. Gott strafe England! -- ch. 5. The american armory -- pt. 2. Final crossing -- ch. 6. The warning -- ch. 7. Leaving harbor -- ch. 8. The ostrich club -- ch. 9. Fellow passengers -- ch. 10. Inside the U-20 -- ch. 11. "The miraculous draught of fishes" -- ch. 12. Into the war zone -- ch. 13. "Suppose they should sink the Lusitania?" -- pt. 3. An ocean red with blood -- ch. 14. "My God, we are lost" -- ch. 15. "Come at once!" -- ch. 16. A bizarre orchestra of death -- ch. 17. Wave upon wave -- ch. 18. A long lingering moan -- ch. 19. Rescues and recoveries -- ch. 20. The town of the dead -- ch. 21. A Sad and horrible task -- pt. 4. "Remember the Lusitania!" -- ch. 22. The hun's most ghastly crime -- ch. 23. Fool or traitor? -- ch. 24. No longer neutral spectators -- ch. 25. German agents are everywhere -- ch. 26. The Kaiser's business only -- ch. 27 "That story is forever disposed of" -- ch. 28. Diving into the wreck -- pt. 5. Willful murder? -- ch. 29. A legitimate target? -- ch. 30. Harm's way -- ch. 31. Anglo-Saxon attitudes -- ch. 32. The U-boat diary -- ch. 33. A new barbarism -- Epilogue -- appendix A. The Lusitania in facts and figures -- appendix B.A technical account of the sinking -- Acknowledgments -- Notes and sources -- Bibliography -- Art credits -- Index.
Includes bibliographical references (p. 502-510) and index.
Keywords: Lusitania (Steamship); World War, 1914-1918 -- Naval operations, German; World War, 1914-1918 -- Naval operations -- Submarine; Shipwrecks -- History -- 20th century; World War, 1914-1918 -- Great Britain; World War, 1914-1918 -- United States; Shipwrecks; World War, 1939-1945 -- Naval operations -- Submarine; Lusitania-Zwischenfall